Next Generation Culture Platforms for Reliable In Vitro Models Methods and Protocols - Brevini, Tiziana A.L; Fazeli, Alireza; Turksen, Kursad (Methods in Molecular Biology, 2021)
XII, 307 p. 69 illus., 59 illus. in color.